A racionalização da experiência de Deus no Calvinismo da Reta Doutrina - Anéas, André (2018)
The process of rationalizing the experience of God is analyzed in the object of this research: Calvinism of the Right Doctrine. The individual who has had a mysticalreligious experience is subjected to the working of a type of religious community which privileges the confession of right doctrine as a decisive element in understanding whether the believer is, in fact, a saved person. The experience of faith is therefore underprivileged, in relation to rational and cognitive aspects duly systematized in doctrinal confessions. The proposed research analyzes the symptoms and causes of the rationalization process. The great question to be answered is whether the “orthodox”, “traditional”, “biblical”, “evangelical”, and “reformed” theology of Calvinism of the Right Doctrine is in fact a shadow that hides rationalization of the experience of God, fruit of the influence of elements of the dynamics of religion and the decontextualization of the apologetic role and sociopolitical context of Protestant scholasticism, provoking imbalance between propositional faith and experiential faith. The answer is positive. Analyzing the period of protestant scholasticism, it is possible to perceive elements that disfavor any kind of experience of God, because reason is privileged in the form of doctrinal systematizations and faith confessions, whose role is to eliminate any doubt that a subversive experience of the faithful can generate in the rigid system of thought of this protestantism. Doubt is a mortal enemy of the “absolute truth” that is sustained and protected by a theory of protestant knowledge, whose origin is in the past. It is a type of protestantism that has the present crystallized, a nostalgic feeling and that has in its enemies an agent that constitutes its own identity. In Calvinism of the Right Doctrine to experience the not tamed sacred is to take risks. To think differently from established orthodoxy is liable to the worst kind of accusation: heresy